2023
DOI: 10.1039/d3qi00937h
|View full text |Cite
|
Sign up to set email alerts
|

Study on the incorporation of various elements into the Keggin lacunary-type phosphomolybdate [PMo9O34]9− and subsequent purification of the polyoxometalates by nanofiltration

Abstract: Transition-metal substituted Keggin-type polyoxometalates (POMs) are of great interest for applications in biomedicine, material science and catalysis. The synthesis of transition metal-substituted Keggin-type polytungstates via the formation of a lacunary...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…The distance is comparable to the O–Na distance between a Keggin-type anion and its Na + counterions (2.986 Å), which we observed in a recently published crystal structure of Na 6 [PV 3 Mo 9 O 40 ] (deposition number 2205007). 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance is comparable to the O–Na distance between a Keggin-type anion and its Na + counterions (2.986 Å), which we observed in a recently published crystal structure of Na 6 [PV 3 Mo 9 O 40 ] (deposition number 2205007). 21…”
Section: Resultsmentioning
confidence: 99%
“…On each metal atom is one terminally coordinated oxo ligand with partial double bond character as indicated by a shortened bond length. 5,12,19–21 The stabilizing effect caused by P( v ) in the Keggin-type POMs goes so far that a substitution of the addenda framework metal with other elements such as vanadium( v ), niobium( v ), iron( iii ), manganese( ii ), cobalt( ii ) etc . is possible without compromising the structural integrity of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Those investigations will lead to a more efficient and selective process for the valorization of humins and thus facilitating separation processes. Previous studies have shown that nanofiltration is a promising downstream process for homogeneously catalyzed reactions using POMs. ,, The use of nanofiltration as a downstream process for the oxidative valorization of humins could also be an integral part of further investigations. Nevertheless, the present comprehensive study provides important insights into structure–activity–selectivity relationships of various functional groups and bonding types as well as the tailoring of POM catalysts, thereby providing a promising basis for further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of niobium (Nb) into the POM catalyst was achieved by a novel synthesis approach using a lacunary Keggin-type structure according to the literature . According to this procedure, sodium molybdate dihydrate (9 equiv) and disodium hydrogen phosphate (1 equiv) were dissolved in water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation